Identifying the key genes of Epstein–Barr virus‐regulated tumour immune microenvironment of gastric carcinomas. Issue 3 (14th December 2022) - Zhou, Heng; Jing, Shuili; Liu, Yu; Wang, Xuming; Duan, Xingxiang; Xiong, Wei; Li, Ruohan; Peng, Youjian; Ai, Yilong; Fu, Dehao; Wang, Hui; Zhu, Yaoqi; et al.
Abstract: The Epstein–Barr virus (EBV) is involved in the carcinogenesis of gastric cancer (GC) upon infection of normal cell and induces a highly variable composition of the tumour microenvironment (TME). However, systematic bioinformatics analysis of key genes associated with EBV regulation of immune infiltration is still lacking. In the present study, the TCGA and GEO databases were recruited to analyse the association between EBV infection and the profile of immune infiltration in GC. The weighted gene co‐expression analysis (WGCNA) was applied to shed light on the key gene modules associated with EBV‐associated immune infiltration in GC. 204 GC tissues were used to analysed the expression of key hub genes by using the immunohistochemical method. Real‐time PCR was used to evaluate the association between the expression of EBV latent/lytic genes and key immune infiltration genes. Our results suggested that EBV infection changed the TME of GC mainly regulates the TIICs. The top three hub genes of blue (GBP1, IRF1, and LAP3) and brown (BIN2, ITGAL, and LILRB1) modules as representative genes were associated with EBV infection and GC immune infiltration. Furthermore, EBV‐encoded LMP1 expression is account for the overexpression of GBP1 and IRF1. EBV infection significantly changes the TME of GC, and the activation of key immune genes was more dependent on the invasiveness of the whole EBV virion instead of single EBV latent/lytic gene expression. Abstract : The lytic EBV virion infects host cells, activates the immune response of the host and promotes the expression of associated key hub genes. Then EBV establishes latent infection in host cells and expressed LMP1, which promotes activation of the NF‐κB signalling pathway and expression of GBP1 and IRF1.